Male circumcision and Mycoplasma genitalium infection in female partners: a randomised trial in Rakai, Uganda. (20th November 2013) - Tobian, Aaron A R; Gaydos, Charlotte; Gray, Ronald H; Kigozi, Godfrey; Serwadda, David; Quinn, Nicole; Grabowski, Mary K; Musoke, Richard; Ndyanabo, Anthony; Nalugoda, Fred; Wawer, Maria J; Quinn, Thomas C
Abstract : Objective: Previous randomised trial data have demonstrated that male circumcision reduces Mycoplasma genitalium prevalence in men. We assessed whether male circumcision also reduces M genitalium infection in female partners of circumcised men. Methods: HIV-negative men were enrolled and randomised to either male circumcision or control. Female partners of male trial participants from the intervention (n=437) and control (n=394) arms provided interview information and self-collected vaginal swabs that were tested for M genitalium by APTIMA transcription-mediated amplification-based assay. Prevalence risk ratios (PRR) and 95% CI of M genitalium prevalence in intervention versus control group were estimated using Poisson regression. Analysis was by intention-to-treat. An as-treated analysis was conducted to account for study-group crossovers. Results: Male and female partner enrolment sociodemographic characteristics, sexual behaviours, and symptoms of sexually transmitted infections were similar between study arms. Female M genitalium prevalence at year 2 was 3.2% (14/437) in the intervention arm and 3.6% (14/394) in the control arm (PRR=0.90, 95% CI 0.43 to 1.89, p=0.78). In an as-treated analysis, the prevalence of M genitalium was 3.4% in female partners of circumcised men and 3.3% in female partners of uncircumcised men (PRR=1.01, 95% CI 0.48 to 2.12, p=0.97). Conclusions: Contrary to findings in men, male circumcision did not affect M genitalium infection in female partners.